2019
DOI: 10.1002/ange.201907773
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride Membranes with a Distinct Nanoconfinement Effect for Efficient Ethylene/Ethane Separation

Abstract: AB Nm embrane with ad istinct nanoconfinement effect toward efficient ethylene/ethane separation is presented. The horizontal and inclined self-assembly of 2D BN nanosheets endowt he BN membrane with abundant percolating nanochannels,a nd these nanochannels are further decorated by reactive ionic liquids (RILs) to tailor their sizes as well as to achieve nanoconfinement effect. The noncovalent interactions between RIL and BN nanosheets favor the ordered alignment of the cations and anions of RIL within BN nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…It also used to suppress side reactions, improving the interfacial contact between the electrode and electrolyte. [87][88][89] As the core of energy materials, porous materials are under constant development, where covalent organic framework (COF) has been designed as one of the new porous materials. 2D COF is one kind of porous polymer nanosheets which have highly crystalline structures, tunable function, and high chargecarrier transfer ability.…”
Section: Other 2dmsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also used to suppress side reactions, improving the interfacial contact between the electrode and electrolyte. [87][88][89] As the core of energy materials, porous materials are under constant development, where covalent organic framework (COF) has been designed as one of the new porous materials. 2D COF is one kind of porous polymer nanosheets which have highly crystalline structures, tunable function, and high chargecarrier transfer ability.…”
Section: Other 2dmsmentioning
confidence: 99%
“…It also used to suppress side reactions, improving the interfacial contact between the electrode and electrolyte. [ 87–89 ]…”
Section: Fundamentals Of 2dms For Asslbsmentioning
confidence: 99%
“…However, perdurable stability and sensitivity to the environment are the main disadvantages of these membranes. In this context, a study suggested by Dou et al revealed that BN membranes obtained by filtration assistance were found to be promising since BN has great thermal and chemical stability . Without considering the detailed mechanism of fabrication, the membranes are obtained through the vacuum filtration of BN nanochannels onto the Nylon support, and asubsequent spin coating of the reactive ionic liquid (RIL) nanoconfinement in BN nanochannels, as is shown in Figure a.…”
Section: Fabrication Techniques Of Bn-based Membranesmentioning
confidence: 99%
“…However, Pt‐based materials face major commercialization challenges including high cost, limited resources, poor durability, and tolerance to poisoning 2‐4 . Therefore, it is necessary to find nonprecious metal‐based catalysts with low price, high activity, and high stability instead of the Pt catalyst 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Therefore, it is necessary to find nonprecious metal-based catalysts with low price, high activity, and high stability instead of the Pt catalyst. 5,6 Transition metal-nitrogen-carbon materials (M-N-C,…”
mentioning
confidence: 99%